Factors affecting the ownership of low-cost housing For socio-economic development in Malaysia - Mohd-Rahim, Faizul Azli; Zainon, Nurshuhada; Sulaiman, Syazwanie; Lou, Eric; Zulkifli, Nurul Hidayah; Ayob, Mohd Fairullazi (Universiti Kebangsaan Malaysia & Royal Institution of Surveyors Malaysia, 2019)
Malaysian government has a special commitment to provide the adequate, affordable housing and quality to all income levels, particularly for low-income group. Over the recent years, Malaysian property market was not balance in terms of supply and demand, where the demand is exceeding supply especially for low-cost housing. However, high demand for housing in urban areas could affect the homeownership issue for low-income group. The first objective of this paper is to study the relationship between household income and housing affordability. Besides, the second objective is to examine housing satisfaction level by the residents focusing on the public low-cost flats under the supervision of Kuala Lumpur City Hall. A survey has been carried out using questionnaires distributed to 500 residents of the three-low-cost housing in Kuala Lumpur, Malaysia. The finding contributes to an establishment of a strategy to improve homeownership of the low-income earners to own PPR house. This study is recommended that more effort should be taken by the government to improve quality of house to ensure the better life of low-income population in the current PPR flats.